PERANCANGAN APLIKASI SISTEM INFORMASI PENDISTRIBUSIAN TENAGA LISTRIK CONTACT CENTER PLN 123 SITE DISTRIBUSI JAKARTA BERBASIS WEB - Ifan Junaedi; Suyantapa Suyantapa (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
ABSTRACTApplication information distribution of web-based power on Contact Center PLN123. The author builds information applications for the distribution of electricity for customers and society. Writing this thesis is inspired from customers or people who are in desperate need of information related to power outage and is based on the author's life experience. The authors choose the information distribution of electric power as a target user because it considers the difficulty of reporting process and information related to power outages that occur. To overcome these obstacles, the authors designed an application of information distribution of web-based electric power that aims to process reports and information blackouts become easier on time because it can be accessed anywhere and anytime. This app can still be refined to improve the quality of future applications.Â Keywords: System Design Analysis, Application, Distribution, Extinguishing, Electric Power